A STUDY USING THE THEORY OF PLANNED BEHAVIOUR TO ANALYZE PURCHASE INTENTION AND ACTUAL PURCHASE TOWARDS GREEN COSMETICS IN PONTIANAK - Mirhad, Yulia Mirhard B1024141004 (Jurnal Manajemen Update, 2018)
The purpose of this research is to analyze Purchase Intention and Actual Purchase towards Green Cosmetics in Pontianak by using the Theory of Planned Behaviour as the awareness of global community towards environmental issues has been rapidly increasing. These days, the market for green product is expanding worldwide in a variety of industries, such as food, fashion and cosmetics. There have been huge increases in encouragement across the world to market natural cosmetic as customers are shifting back form chemical ingredients cosmetic to more natural cosmetics. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The sample of this research is consumers in Pontianak who are above 18 years old and used green cosmetics for the last six months. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1: There is significant relationship between attitude and purchase intention, H2: There is significant relationship between subjective norms and purchase intention, H3: There is significant relationship between perceived behavioural control and purchase intention, H4: There is significant relationship between perceived behavioural control and actual purchase, H5: There is significant relationship between purchase intention and actual purchase. The result of this research shows that H1, H3, H5 are accepted but H2 and H4 are rejected. Keyword : green cosmetics, theory of planned behaviour, green products, purchase intention, actual purchaseBIBLIOGRAPHIES Ajzen, I., 1991. The Theory of Planned Behaviour. Organizational Behaviour and Human Decision Processes, 50, 179-211. Che Hsu, I Huang, Ming Hsu, and Hsuan Huang (2016). A study on Behavioural Model on Green Consumption. Journal of Economics, Business and Management, 4(5), 372-377.Fred R. David, 2011. Strategic Management Concepts and Cases 13th edition. Prentice Hall, New Jearsey. Han, Jane and Sheu, 2010. Application of the Theory of Planned Behaviour to green hotel choice: Testing the effect of environmental friendly activities. Tourism Management, 31, 325-334. Hsu, Chang, Yansritakul, 2017. Exploring Purchase Intention of Green Skincare Products Using the Theory of Planned Behaviour: Testing the Moderating Effects of Country of Origin and Price Sensitivity. Journal of Retailing and Consumer Services, 34, 145-152. Joong Kim, Njite, Hancer, 2013. Anticipated Emotion in Consumers? Intentions to Select Eco-friendly Restaurants: Augmenting the Theory of Planned Behaviour. International Journal of Hospitality Management, 34, 255-262. J. Supranto, 1997. Metode Riset dan aplikasinya didalam pemasaran edisi enam. Penerbit Fakultas Ekonomi Universitas Indonesia, Jakarta. Kalafatis, Pollard, East and Tsogas, 1999. Green Marketing and Ajzen?s Theory of Planned Behaviour: A Cross examination. Journal of Consumer Marketing, 16 (5), 441-460. Hair, Anderson, Tatham and Black, 1998. Multivariate Data Analysis International edition 5th edition. Prentice Hall. Paul, Modi and Patel (2016). Predicting green product consumption using theory of planned behavior and reasoned action. Joural of Retailing and Consumer Services, 29, 123-134. Wu and Chen ,2014. A Model of Green Consumption Behaviour Constructed by the Theory of Planned Behaviour. International Journal of Marketing Studies, 6(5), 119-128. Web References:Liputan6 news, 2017. Body Shop Indonesia fokus pada pemasaran digital [online]. Available at:http://tekno.liputan6.com/read/2866199/body-shop-indonesia-fokus-pada-pemasaran-digital [Accessed on 2nd January 2017]. Badan pengawas obat dan makanan Republik Indonesia, 2017. Siaran Pers Badan POM RI dukung daya saing produk kosmetik indonesia[online]. Available at:https://www.pom.go.id/new/view/more/pers/387/SIARAN-PERS-Badan-POM-RI-Dukung-Daya-Saing-Produk-Kosmetik-Indonesia.html [Accessed on 2nd January 2017]. Martha Tilaar, 2015. PT Martina Berto , TBK received Ecocert Certification [online]. Available at:http://www.marthatilaargroup.com/en/news/news-update/408-pt-martina-berto,-tbk-received-ecocert-certification.html [Accessed on 2nd January 2017]. Suara Karya, 2014. Pasar global produk ramah lingkungan [online]. Available at:http://www.kemenperin.go.id/artikel/8810/PasarGlobal-Produk-Ramah-Lingkungan [Accessed on 2nd January 2017]